IEEE PES Innovative Smart Grid Technologies 2012
DOI: 10.1109/isgt-asia.2012.6303190
|View full text |Cite
|
Sign up to set email alerts
|

Planning of a Grid-connected Smart Micro-power system

Abstract: In this paper, planning of a grid-connected smart micro-power system is investigated. At first, its Advanced Metering Infrastructure (AMI) is designed to record, process and communicate the micro-grid energy, electrical data (e.g., active and reactive power flow data, voltage, frequency etc.), wind speed, solar radiation and so on, which are sent to the Data-Processing and Management center (DPMc) via the designed communication system. The DPMc analyses the data and manage the network using two software packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study using EnegyPLAN [29] showed a significant contribution of demand response as a moderation strategy to reduce energy imbalances and to an increase of wind power penetration into a national energy system. HOMER has been used mainly for planning renewable micro grids [30,31] and their optimal sizing [7,[32][33][34][35][36][37][38] based on the minimal levelized costs of energy (COE) and net present costs (NPC) criteria under different constraints. Its suitability for Serbia was proven by a comparison of measurement data [39].…”
Section: Demand Response As Part Of a Planning Methodologymentioning
confidence: 99%
“…A study using EnegyPLAN [29] showed a significant contribution of demand response as a moderation strategy to reduce energy imbalances and to an increase of wind power penetration into a national energy system. HOMER has been used mainly for planning renewable micro grids [30,31] and their optimal sizing [7,[32][33][34][35][36][37][38] based on the minimal levelized costs of energy (COE) and net present costs (NPC) criteria under different constraints. Its suitability for Serbia was proven by a comparison of measurement data [39].…”
Section: Demand Response As Part Of a Planning Methodologymentioning
confidence: 99%
“…), and economic data (interest rate, useful life, etc.). This study employed the Hybrid Optimization Model for Electric Renewables (HOMER), which is a simulation tool and is widely used to plan optimal microgrids [20][21][22][23], to determine whether to maintain an on-grid energy system or to setup an independent off-grid system in Jin-do and Wanddo. After simulating and optimizing the hybrid system configured to compare, HOMER can be used for the sensitivity analysis to input values that should be analyzed more [24,25].…”
Section: Introductionmentioning
confidence: 99%